2011
DOI: 10.1093/aje/kwr250
|View full text |Cite
|
Sign up to set email alerts
|

Prepregnancy Body Mass Index and Gestational Weight Gain in Relation to Child Body Mass Index Among Siblings

Abstract: There is increasing evidence that in utero effects of excessive gestational weight gain may result in increased weight in children; however, studies have not controlled for shared genetic or environmental factors between mothers and children. Using 2,758 family groups from the Collaborative Perinatal Project, the authors examined the association of maternal prepregnancy body mass index (BMI) and gestational weight gain on child BMI at age 4 years using both conventional generalized estimating equations and fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 26 publications
5
73
1
Order By: Relevance
“…Although we assessed maternal BMI only at the time of study, we should note a possibility that maternal prepregnancy BMI or gestational weight gain could be rather important determinants of early childhood overweight [35][36][37] . To examine the robustness of the present findings, we conducted the analyses without adjusting for maternal BMI, which did not substantially change the results; compared with children of non-working mothers, the ORs among children whose mothers work <8 h/day and ≥8 h/day were 0.26 (95% CI: 0.08, 0.82) and 0.68 (95% CI: 0.20, 2.31), respectively, in model 5.…”
Section: Discussionmentioning
confidence: 99%
“…Although we assessed maternal BMI only at the time of study, we should note a possibility that maternal prepregnancy BMI or gestational weight gain could be rather important determinants of early childhood overweight [35][36][37] . To examine the robustness of the present findings, we conducted the analyses without adjusting for maternal BMI, which did not substantially change the results; compared with children of non-working mothers, the ORs among children whose mothers work <8 h/day and ≥8 h/day were 0.26 (95% CI: 0.08, 0.82) and 0.68 (95% CI: 0.20, 2.31), respectively, in model 5.…”
Section: Discussionmentioning
confidence: 99%
“…Further, pediatricians see many women who plan to have more children and thus they are in a unique place to inform women of the benefits of reducing the pre-pregnant BMI before conceiving, the role of physical activity in pregnancy on later age at menarche of the daughter, and the detrimental effects of pre-pregnancy overweight and obesity on risk of obesity for the future offspring. 7 In addition to messages about the importance of diet and physical activity, pediatricians already convey cancer prevention messages through regular reminders about the use of sunscreen at annual child visits as well as the harms from smoking. Although it is often challenging to measure the full impact of pediatricians' prevention guidance, the essential role that they play in lifelong cancer prevention cannot be denied when one considers the concrete example of their role in increasing the uptake of the human papillomavirus cancer vaccine.…”
Section: Annual "Well Baby" Examinationsmentioning
confidence: 99%
“…A few studies have used a between-sibling design to unravel intrauterine effects from genetic and lifestyle influences, with conflicting results. [21][22][23] One study reported that the GWG-childhood overweight associations are completely explained by behavioral and environmental factors, 21 and another study concluded that GWG is associated with child's weight, independent of behavioral and environmental factors. 22 Besides differences in age of outcome between the 2 studies, the conclusion may also differ according to maternal prepregnancy BMI: 1 study concluded that most of the GWG-offspring overweight association was explained by lifestyle and genetic factors in normal weight mothers, and there was a contribution of intrauterine programming in overweight mothers.…”
Section: Comparison With Earlier Studies and Interpretationmentioning
confidence: 99%